2022
DOI: 10.31219/osf.io/6bgqh
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exposure to Untrustworthy Websites in the 2020 US Election

Abstract: Prior research has documented exposure to fake news and online misinformation using large- scale data on individuals’ media use, which has provided important information about the scope and nature of people’s exposure to misinformation online. However, most of this work has made use of data collected during the 2016 US election, and far fewer studies have examined how exposure to misinformation online has changed since 2016. In this paper, we examine exposure to untrustworthy websites in the lead up to the 202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(44 citation statements)
references
References 31 publications
4
39
1
Order By: Relevance
“…in the browsing data by matching the domains the participants visited with a list of known misinformation sites (Moore et al 2022). We also conducted a supplemental analysis where we only examined misinformation website visits that refer specifically to the election, finding similar results (see Supporting Information E).…”
Section: Resultsmentioning
confidence: 85%
See 3 more Smart Citations
“…in the browsing data by matching the domains the participants visited with a list of known misinformation sites (Moore et al 2022). We also conducted a supplemental analysis where we only examined misinformation website visits that refer specifically to the election, finding similar results (see Supporting Information E).…”
Section: Resultsmentioning
confidence: 85%
“…One crucial question that remains surprisingly understudied is how exposure to misinformation online affects downstream beliefs . For example, while recent research has revealed that millions of Americans were exposed to misinformation on the internet during the 2016 (e.g., Allen et al 2020; and 2020 (Moore et al 2022) elections, it is unclear how these exposures influenced people's beliefs about the election.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This may have impacted the spread of and engagement with misinformation during the 2016 presidential election in the United States, during which time prior work found that older adults were heavily engaged with, exposed to, or shared misinformation on Twitter in 2019 (Grinberg et al 2019), and seven times more likely to share information from fake news sources on Facebook (Guess, Nagler, and Tucker 2019). This trend has persisted, with studies examining the period between 2016 and 2018 (Allen et al 2020) as well as the period leading up to the 2020 presidential election in the United States (Moore, Dahlke, and Hancock 2022) continuing to find that older adults are more likely to read or visit websites containing misinformation.…”
Section: Related Workmentioning
confidence: 99%